Cross sectional analysis of factors associated with leptospirosis cases treated at district general hospital, Matara, Sri Lanka during 2015-2018 - Samaraweera, Nayana Y.; Karunaratne, Upali; Mediwaka, Malkanthi K.; Patabendige, Deepika; Jagathpathi, Janaka; Wijayasiriwardhana, Buddhini S.; Senanayake, Deepthi; Amarasiri, Sheran; Wanniarachchi, Somarathna (International Journal of Advances in Medicine, 2022)
Background: Leptospirosis is a zoonotic illness with a global disease burden impacting both developed and developing nations and is caused by pathogenic spirochetes of the genus Leptospira. In this study, selected characteristics of confirmed leptospirosis cases were studied; hence modifiable risk factors were elucidated. This information would be useful to prevent further transmission of leptospirosis by public health care workers in Sri Lanka and take appropriate administrative decisions regarding leptospirosis control in the community. Methods: This was a descriptive cross sectional survey of Bed Head Tickets (BHTs), Case Surveillance Forms of confirmed leptospirosis cases treated at district general hospital, Matara during 2015-2018. The study was conducted from 21.02.2019 to 01.03.2019. Results: Age >35 years (OR 3.92:, 95% CI:2.72-5.65), male sex (OR:2.30, 95% CI:1.61-3.29), paddy field as source of infection (OR:2.45, 95% CI:1.69-3.54), positive history of recent skin lesions/injury (OR:2.29, 95% CI:1.58-3.34), (OR:3.14, 95% CI:1.62-6.06), (OR:2.88, 95% CI:1.31-6.36), (OR:2.13, 95% CI:1.27-3.58) were risk factors for leptospirosis. Positive history of chemo prophylactic treatment (doxycycline administration) and its duration were not associated with leptospirosis Conclusions: Age >35 years (OR 3.92:, 95% CI:2.72-5.65), male sex (OR:2.30, 95% CI:1.61-3.29), paddy field as source of infection (OR:2.45, 95% CI:1.69-3.54), positive history of recent skin lesions/injury (OR:2.29, 95% CI:1.58-3.34) were risk factors for leptospirosis.